(untitled) (Damascus University Journal for engineering sciences, 2022)
This research aims to know the maintenance costs of the upper limb prostheses and the most common malfunctions by conducting a retrospective study of the upper limb amputee’s records in the center of rehabilitation and prosthetics in Damascus during the period between 2018-2021. In addition to a demographic characterization of the amputees of the upper limbs during the study period. The research adopted the descriptive approach for the retrospective study so the researchers collected data from electronic and paper records in the center of rehabilitation and prosthetics and then studied them using descriptive statistics. The number of visits recorded during the research period was 429 visits by 332 patients. The most common cause of amputation was war injuries among the participants, while the most common level of amputation was below-elbow amputation. Amputees used passive prostheses by 70.39% compared to body-powered prostheses. The most replaced parts of upper limb prostheses were: cover, hand assembly, and suspension straps(harness). The annual cost average is 30,700 US for upper limbs. The cost is affected by the type of prosthesis and level of amputation. The conclusion: upper limb amputees depend an passive prostheses. These prostheses have a Axed annual cost of replacing the cover and hand a ssembly. This study was limited to the costs of limb manufacture and maintenance. It is necessary to follow up the study by studying the cost of the upper limb prosthesis life cycle. Besides, expanding the field of study to include the reality and cost of maintaining the lower limb prosthetics and orthotics.